2014
DOI: 10.1080/15564886.2014.941520
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control and Lifestyles: Associations to Juvenile Offending, Violent Victimization, and Witnessing Violence

Abstract: The extent to which well-established theories of offending apply to violent victimization is increasingly studied. Measures of indirect victimization are rarely included in this literature. This study examined the concurrent relation of self-control components and lifestyle measures to juvenile offending, direct victimization, and witnessing violence among 233 Hispanic and African American 11th-grade students. Findings revealed strong support for the role of a deviant lifestyle; support for prosocial lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…The current results parallel findings from previous studies over the overlap in victimization and offending examining aspects of lifestyle and routine activities. Consistent with Klevens et al (2002) and Wiesner and Rab (2015), the demographic traits as well as lifestyles of respondents in our study increased their likelihood of offending and risk of victimization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results parallel findings from previous studies over the overlap in victimization and offending examining aspects of lifestyle and routine activities. Consistent with Klevens et al (2002) and Wiesner and Rab (2015), the demographic traits as well as lifestyles of respondents in our study increased their likelihood of offending and risk of victimization.…”
Section: Discussionsupporting
confidence: 92%
“…Further examination of lifestyle measures as predictive of both offending and direct victimization was conducted by Wiesner and Rab (2015). Analyzing survey responses from 233 Hispanic and African American 11th-grade students, researchers found strong evidence to support the finding that a deviant lifestyle was strongly associated with both offending and victimization (Wiesner and Rab, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have been carried out to test the relationship between low self-control and physical victimization, with studies generally providing support for the link (Flexon, Meldrum, & Piquero, 2015; Turanovic, Reisig, & Pratt, 2015; Wiesner & Rab, 2015). For example, Stewart, Elifson, and Sterk (2004) found that women with low self-control were more likely to be victims in the streets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The works of several authors help us understand the connection between victimization and offending by not only applying these theories to delinquency or victimization separately but by putting their focus directly on the connection between victimization and offending (Berg & Loeber, 2011;Berg, Stewart, Schreck, & Simons, 2012;Cudmore, Cuevas, & Sabina, 2015;Cullen, Unnever, Hartman, Turner, & Agnew, 2008;DeCamp & Newby, 2014;Flexon, Meldrum, & Piquero, 2015;Klevens et al, 2002;Mancini & Pickett, 2015;Posick, 2013;Posick & Zimmerman, 2015;Pyrooz, Moule, & Decker, 2014;Reid & Sullivan, 2012;Taylor, Freng, Esbensen, & Peterson, 2008;Tillyer & Wright, 2014;Zavala & Spohn, 2013;Zimmerman, Farrell, & Posick, 2017;Zweig, Yahner, Visher, & Lattimore, 2015;Wiesner & Rab, 2014). Fewer studies examine the victimoffender overlap from a longitudinal perspective (Barnes & Beaver, 2012;Jennings, Higgins, Tewksbury, Gover, & Piquero, 2010;Melde & Esbensen, 2009;Muftić & Hunt, 2012;Reingle & Maldonado-Molina, 2012;Schreck, Stewart, & Wayne, 2008;Smith & Ecob, 2007;Turanovic & Pratt, 2015;van Gelder, Averdijk, Eisner, & Ribaud, 2015;Zweig et al, 2015).…”
mentioning
confidence: 99%